(untitled) (Architecture Image Studies, 2026)
The development of academic literacy has become a critical concern in Indonesian as a Foreign Language (Bahasa Indonesia bagi Penutur Asing/BIPA) programs, particularly as international students are increasingly required to produce academic texts in Indonesian higher education contexts. This study investigates how writing strategies and genre awareness contribute to the development of academic literacy among BIPA learners. Adopting a qualitative-dominant mixed-methods design, the study involved 15 BIPA students enrolled in an intermediate-to-advanced academic writing course at a public university in Indonesia. Data were collected through academic writing tasks, a writing strategy questionnaire, classroom observations, and semi-structured interviews. Qualitative data were analyzed thematically and through genre analysis, while quantitative data were used descriptively to support qualitative findings. The results reveal that academic literacy development among BIPA learners is shaped by the dynamic interplay of metacognitive writing strategies, genre awareness, and linguistic background. Learners who actively employed global writing strategies—such as planning, monitoring, and substantive revision—demonstrated stronger control over academic genres, particularly in argumentative and research-based writing. However, genre awareness was uneven across task types, with reflective genres being more accessible than analytically demanding academic genres. Linguistic background, especially differences in writing systems, further mediated learners’ ability to realize genre conventions effectively. Overall, the findings underscore that academic literacy in BIPA contexts extends beyond language accuracy to encompass strategic, rhetorical, and sociocultural competencies. This study contributes to L2 writing research by providing empirical evidence from Indonesian higher education and offers pedagogical implications for genre-based and strategy-oriented instruction in BIPA programs.